Fabrication of Ti3SiC2-based composites via three-dimensional printing: Influence of processing on the final properties. Issue 8 (June 2016) - Carrijo, Mylena Mayara Matias; Lorenz, Hannes; Filbert-Demut, Ina; de Oliveira Barra, Guilherme Mariz; Hotza, Dachamir; Yin, Xiaowei; Greil, Peter; Travitzky, Nahum
Abstract: In this work the influence of the processing routes on the microstructure and properties of Ti3 SiC2 -based composites was investigated. The three main processing steps are (i) three-dimensional printing of Ti3 SiC2 powder blended with dextrin, (ii) pressing of printed samples (uniaxial or cold isostatic pressing), and (iii) sintering of pressed samples at 1600 °C for 2 h. The Ti3 SiC2 -based composites were analyzed by X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDS). Young's Modulus and flexural strength were measured to examine the mechanical properties. Porosity, density, shrinkage, and mass change were measured at each processing step. Those samples uniaxially pressed at 726 MPa presented the highest density, shrinkage, and mass change. However, microstructural morphologies were crack-free and homogeneous for cold isostatic pressed Ti3 SiC2 -based composites as compared to uniaxially pressed samples. The highest values for Young's Modulus ( 300 GPa) and flexural strength ( 3 GPa) were observed with uniaxially pressed Ti3 SiC2 -based composites.